Private Debt Overhang and the Government Spending Multiplier: Evidence for the United States - Marco Bernardini; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2015)
Using state-dependent local projection methods and historical U.S. data, we find that government spending multipliers are considerably larger in periods of private debt overhang. In particular, we find significant crowding-out of personal consumption and investment in low-debt states, resulting in multipliers that are significantly below one. Conversely, in periods of private debt overhang, there is a strong crowding-in effect, while multipliers are much larger than one. In high-debt states, more (less) government purchases also reduce (increase) the government debt-to-GDP ratio. These results are robust for the type of government spending shocks, and when we control for the business cycle, government debt overhang and the zero lower bound on the nominal interest rate. Our findings imply that spending multipliers were likely much larger than average during the Great Recession.
Keywords: C32; E32; E62; N12; 330; government spending multipliers; drivers; private debt